Digital Accounting Implementation In Sales Transactions In Indomaret In Nginden Jangkungan Surabaya - Elmiano AE Erong; Ahmad Q. Izzuddin; Krisogonus A. Seleman; Maria Yovita R. Pandin (Jurnal Riset Akuntansi, 2023)
The purpose of this study is to explain the implementation of digital accounting in sales transactions. The type of research conducted in this research is qualitative with the research object, namely Indomaret, which is in the Nginden Jangkungan Village. This research was conducted in April 2023 using a qualitative method by presenting data and drawing conclusions. The type of data used is primary data or data obtained directly from Indomaret employees who were on duty when the researchers conducted interviews and observations. The number of informants in this study were five people taken from five Indomaret located in the Nginden Jangkungan Village. After going through the research process, researchers can state that at Indomaret outlets one of the digital accounting components has been implemented.